Biofuels - Demirbas, Ayhan (Springer, 2017)
Biofuel is a renewable energy source produced from natural (biobased) materials, which can be used as a substitute for petroleum fuels. The benefits of biofuels over traditional fuels include greater energy security, reduced environmental impact, foreign exchange savings, and socioeconomic issues related to the rural sector. Furthermore, biofuel technology is relevant to both developing and industrialized countries. For these reasons, the share of biofuels in the automotive fuel market is expected to grow rapidly over the next decade.